Geriatric morbidity pattern in a tertiary care center in the hilly state of Sikkim - Singh, Kulwant; Dey, Sowmya (International Journal Of Community Medicine And Public Health, 2018)
Background: This study was done to find out geriatric morbidity pattern in a tertiary care hospital in the hilly state of Sikkim. Methods: The study was conducted in Central Referral Hospital, a tertiary care center, in the hilly state of Sikkim, over a period of three months. All geriatric patients, 60 years or above, were included in the study. Morbidity affecting specific organ systems was classified based on the outpatient department (OPD) visited and case files of those patients. Results: 215 elderly patients visited outpatient department during the study period. Morbidity related to eyes was most common followed by cardiovascular, gastrointestinal and respiratory systems. Conclusions: Our study compares well with range of distribution of complaints in other studies. However, there is a wide range of proportionate distribution of different morbidities in different geographic areas of our country. Hence, before deciding about resource allocation for geriatric health facilities related to different specialties, distribution of morbidities should be determined for that region.